Targeted inhibition of protein synthesis renders cancer cells vulnerable to apoptosis by unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (Cell Death & Disease, 2023)
Cellular stress responses including the unfolded protein response (UPR) decide over the fate of an individual cell to ensure survival of the entire organism. During physiologic UPR counter-regulation, protective proteins are upregulated to prevent cell death. A similar strategy induces resistance to UPR in cancer. Therefore, we hypothesized that blocking protein synthesis following induction of UPR substantially enhances drug-induced apoptosis of malignant cells. In line, upregulation of the chaperone BiP was prevented by simultaneous arrest of protein synthesis in B cell malignancies. Cytotoxicity by immunotoxins—approved inhibitors of protein synthesis—was synergistically enhanced in combination with UPR-inducers in seven distinct hematologic and three solid tumor entities in vitro. Synergistic cell death depended on mitochondrial outer membrane permeabilization via BAK/BAX, which correlated with synergistic, IRE1α-dependent reduction of BID, accompanied by an additive fall of MCL-1. The strong synergy was reproduced in vivo against xenograft mouse models of mantle cell lymphoma, Burkitt’s lymphoma, and patient-derived acute lymphoblastic leukemia. In contrast, synergy was absent in blood cells of healthy donors suggesting a tumor-specific vulnerability. Together, these data support clinical evaluation of blocking stress response counter-regulation using inhibitors of protein synthesis as a novel therapeutic strategy.
CRIS-Team Scopus Importer:2023-09-08